División político-administrativa y representación política en el gobierno de ciudad. Un análisis histórico-territorial comparativo de Londres, Medellín y Río de Janeiro (2015)
ABSTRACT: The aim of this work is to show how get unfolded the relationship between municipal territorial configuration and politic representation in three cities —London, Rio de Janeiro and Medellin—, with the purpose to explore the conditions and historical-territorial processes that have enabled or inhibited political and administrative decentralization and citizen participation in the municipal government and in their respective sub-municipal territorial units, call them comunas, boroughs or Administrative Regions. We start problematizing the notions of political and administrative decentralization and citizen participation from the perspective of territorial political community (polity), category where we integrate contributions and discussions of authors such as Dahl, Castoriadis, Raffestin, Habermas, Lefebvre and Harvey. After that we show the current disposition of the politicaladministrative division of each city, comparing how are or not shaped areas of citizen participation and political representation into their jurisdictions. Given the large differences observed, the work proceeds in a historical and territorial examination of the political-regulatory national contexts and territorial processes in the formation of urban and municipal political space in each city, examining the existence or not of historical matrices of territorial production and political participation that helps to explain these differences.